Initial permeability of the 19-day foetus to nickel (Revista Española de Fisiología, 1989)
The administration of 63NiCl2 to 19-day pregnant rats produced a limited transfer of nickel to the foetus.An experimental model based on the incubation of the conceptuses still connected to the maternal organism resulted in an appreciable net transfer of nickel through the amniotic membranes.The placenta retained a significant amount of radioactive nickel as did the lining of the uterine wall.The circulation of nickel through the foetus following the direction maternal blood—-placenta—-foetus—-amniotic membranes—-endometrium—-maternal venous blood, is postulated.This transfer could provide an additional protection to placental barrier against metal toxicity.